Le importazioni di merci lusitane nel porto di Olbia (Sardegna meridionale) - Nervi, Cristina (Rei Cretariae Romanae Fautorum Acta, 2022)
Olbia is the main port on the eastern coast of Sardinia. It is settled in a gulf, which allowed the development of an important market since the Phoenician period. In the Late Roman period cargoes from the whole Mediterranean area (Hispania, Levant, Italic Peninsula, Calabria, Sicily, Africa and Gaule) joined the port. The Lusitanian products arrived at Olbia since the 1st century AD. Particularly interesting are the Late Roman imports; in the 4th and 5th century AD the lusitanian amphoras reached Olbia, carrying fish products. This paper deals with Olbia‘s Lusitanian fish products, focusing on the amphorae found at the excavations of the old port of the town.